To solve the quadratic equation \( x^2 + 4x = 41 \) by completing the square, follow these steps:
-
Move constant to the other side:
\[ x^2 + 4x - 41 = 0 \] -
Complete the square:
Take the coefficient of \( x \) (which is 4), halve it (which gives you 2), and square it (which gives you 4). Add and subtract this value on the left side:
\[ x^2 + 4x + 4 - 4 - 41 = 0 \implies (x + 2)^2 - 45 = 0 \]This simplifies to:
\[ (x + 2)^2 = 45 \] -
Take the square root of both sides:
\[ x + 2 = \pm \sqrt{45} \] -
Isolate \( x \):
\[ x = -2 \pm \sqrt{45} \]Note that \( \sqrt{45} = 3\sqrt{5} \), so we can simplify it: \[ x = -2 \pm 3\sqrt{5} \]
-
Final answer:
\[ x = -2 + 3\sqrt{5}, \quad -2 - 3\sqrt{5} \]
Therefore, the correct response is: x = −2 + 3√5, −2 − 3√5.